Do you know this syndrome? - Alexandre Moretti de Lima; Vitor Arantes Sperandio; Sheila Pereira da Rocha; Beatriz Medeiros de Ribeiro; Carmelia Matos Santiago Reis (Sociedade Brasileira de Dermatologia, 2013)
The hyperimmunoglobulin E syndrome, or Job's syndrome is a rare primary immunodeficiency characterized by recurrent skin abscesses, recurrent respiratory tract infections, and high levels of IgE, eosinophilia, bone and dental changes. We report the case of a fourteen-year-old male patient presenting this disease, with both typical and also some relatively sporadic manifestations. We performed a literature review on the syndrome and its associated clinical findings.